1997
DOI: 10.1073/pnas.94.22.11777
|View full text |Cite
|
Sign up to set email alerts
|

Making chemistry selectable by linking it to infectivity

Abstract: The link between recognition and replication is fundamental to the operation of the immune system. In recent years, modeling this process in a format of phagedisplay combinatorial libraries has afforded a powerful tool for obtaining valuable antibodies. However, the ability to readily select and isolate rare catalysts would expand the scope of library technology. A technique in which phage infection controlled the link between recognition and replication was applied to show that chemistry is a selectable proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Seminal works in the field of Ab catalysis have shown that Abs with germline configuration are endowed with catalytic functions as diverse as oxy-cope rearrangement (34), Diels-Alder reaction (35,36), or peptide hydrolysis (37,38), thus demonstrating that the catalytic potential of immunoglobulins is encoded in the genome. The observation of amidase activity performed by circulating IgG, IgM, and IgA from healthy donors (39,40), and our finding of baseline levels of FVIII hydrolysis by normal immunoglobulins, indicates that the repertoire of immunoglobulins endowed with catalytic functions is expressed under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seminal works in the field of Ab catalysis have shown that Abs with germline configuration are endowed with catalytic functions as diverse as oxy-cope rearrangement (34), Diels-Alder reaction (35,36), or peptide hydrolysis (37,38), thus demonstrating that the catalytic potential of immunoglobulins is encoded in the genome. The observation of amidase activity performed by circulating IgG, IgM, and IgA from healthy donors (39,40), and our finding of baseline levels of FVIII hydrolysis by normal immunoglobulins, indicates that the repertoire of immunoglobulins endowed with catalytic functions is expressed under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…IVIg exhibited a hydrolytic activity of 55.6 Ϯ 25.9 mol/min/mol toward FVIII, a value statistically indistinguishable from the mean rate of FVIII hydrolysis measured in the case of IgG from nine healthy blood donors (54.9 Ϯ 22.5 mol/min/mol, data not shown). Purified IgG from 21 of the 45 patients (46.6%) included in the study (i.e., patients 1,2,5,8,10,13,14,15,16,17,21,22,23,29,32,35,36,37,41,43, and 45) exhibited a FVIIIhydrolyzing activity that was significantly higher than that of IVIg (Table II, We have previously documented that FVIII-hydrolyzing IgG behave as serine proteases in the absence of contamination by adventitious proteases (8). In this study, the absence of contaminating proteases was confirmed by MALDI-TOF analysis of trypsin digests of the IgG preparations (data not shown).…”
Section: Fviii-hydrolyzing Activity Of Igg From Patients With Acquirementioning
confidence: 99%
“…Two murine catalytic antibodies, 21H3 and 2H6 (15)(16)(17)(18), and one murine anti-cocaine antibody, 92H2 (generated by our laboratory), were used to construct V H -(Gly 4 Ser)-pVII and V L -(Gly 4 Ser)-pIX fusion proteins. The V H sequences in each case were fused to the N terminus of pVII, and the V L sequences were fused to the N terminus of pIX.…”
Section: Construction Of Flag and Pvii͞pix Fusion Proteinsmentioning
confidence: 99%
“…The PCR products were digested by restriction enzymes NcoI and NheI and inserted into the phagemid vector pCGMT (15).…”
Section: Construction Of Flag and Pvii͞pix Fusion Proteinsmentioning
confidence: 99%
See 1 more Smart Citation